The animal in Ottoman Egypt - Mikhail, Alan, 1979- (Oxford University Press, USA, 2013)
Animals in rural Egypt became enmeshed in social relationships and made possible many tasks otherwise impossible. Rather than focus on what animals represented or symbolized, Mikhail discusses their social and economic functions, as Ottoman Egypt cannot be understood without acknowledging animals as central shapers of the early modern world.